The studies on dumping babies among the community of UiTM in Lendu, Alor Gajah Melaka / Nor Azura Abdul Latif and Abdul Muhyi Samsudin - Abdul Latif, Nor Azura; Samsudin, Abdul Muhyi (2012)
This study sought to examine the reason on why baby dumping issue is occurred, the effect of the action and how to curb or avoid this issue from bad to worse and widely spread in the future generation and could even damage our image as a Muslim. This research was carried out by the study of quantitative research based on primary data. The questionnaires are randomly distributed to the community of UiTM that have been divided into non-academic staff. Non-academic staffs are the Hal Ehwal Akademik (HEA), Hal Ehwal Pelajar (HEP), UiTM librarians, security guards and also cleaners in Alor Gajah Melaka campus. A self-administered questionnaire was used as the data collection method and the data have been analyzed by using SPSS 16.0 version. Four main causes was identified that lead to dumping baby issues which are lack of education of religion, moral and ethic, media, society behaviours or perception towards pregnant teenagers and individual itself. All of those causes mostly will contribute the baby dumping issues because the lack of education in religion make the teenagers fell not guilty to dump their baby, lack of social support also make them feel afraid to get the help. In this research also we identified the effects of this issues and certain solutions to reduce this baby dumping issues happened.